Chemical synthesis of a library of natural product-like derivatives based on pinnaic acid and initial evaluation of their anti-cancer activity. Issue 47 (18th November 2022) - Fudger, Alex; Cakir, Okan M.; Khan, Yousaf; Sinclair, Alex; Le Gresley, Adam
Abstract : A library of halichlorine/pinnaic acid novel analogues were synthesised and tested for anti-cancer activity against two cancer cell lines, HeLa and CaCo-2. Twelve compounds displayed anti-cancer activity, with eleven selective for CaCo-2 cells. Abstract : Halichlorine and pinnaic acid have been shown previously to be potent inhibitors of the inflammatory enzymes cPLA2 and VCAM-1 and have also demonstrated some anti-cancer activity. They possess an almost identical azaspirocyclic core consisting of a unique 3-dimensional geometry with four stereocentres, making them compounds of interest for further study to reveal any bioactivity not yet discovered. The azaspirocyclic core was synthesised from an established protocol, from which a small library of novel analogues were synthesised and tested for activity against two cancer cell lines, HeLa and CaCo-2, along with the non-cancerous cell line HaCaT. Eleven compounds were found to be selective for CaCo-2 cells.